2016
DOI: 10.1007/s00784-016-1882-4
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and efficiency study of plant extracts-based bleaching agents

Abstract: These data open new possibilities for the use of new natural products in dental bleaching treatments that can insure significant esthetic results and lower side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…This result allowed us to reject the first hypothesis of this study. These data corroborate with the literature that reports that a sizable proportion of the patients experienced sensitivity during and after bleaching treatment 1 , 3 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result allowed us to reject the first hypothesis of this study. These data corroborate with the literature that reports that a sizable proportion of the patients experienced sensitivity during and after bleaching treatment 1 , 3 .…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study revealed that the bleaching product containing oxalate showed little to no effect on the control and occurrence of dental sensitivity and did not exceed the performance of bleaching agents without desensitizers in any of the tests in this study, which demonstrably showed a lower performance than various products containing these agents 1 . Given this context, we emphasize the systematic review performed by Cunha-Cruz, et al 7 (2011) that concluded that available evidence suggests that oxalates are not effective to decrease sensitivity.…”
Section: Discussionmentioning
confidence: 58%
“…Bleaching agents are effective to remove the staining for the hybrid ceramic when 15% carbamide peroxide or experimental gel was used. The whitening result produced by the two bleaching gels were similar, thus that bleaching agents based on natural products can be regarded as less aggressive alternatives to commercial gels based on carbamide peroxides [16].…”
Section: Figure 1 Correlation Between ∆E Values Obtained After Stainmentioning
confidence: 72%
“…Other studies observed that the effect on the surface of the restorative materials were material dependent. The effects to the pulp were also studied, but with no clinical significance [15,16].…”
mentioning
confidence: 99%
“…Considering the deleterious effects that peroxide bleaching agents bring to the dental structure, some alternatives have already been studied [15][16][17][18][19] . Among them, the cysteine protease enzymes, such as papain and bromelain have been described as active agents with bleaching potential 16,18,19 .…”
mentioning
confidence: 99%